The Effect of Speed Reading to the Students’ Ability in Extensive Reading on Semester III at FKIP UHN Pematangsiantar - Bertaria Sohnata Hutauruk (Journal of English Language and Culture, 2020)
This research aims to determine the effect of applying the effect of speed reading technique on the students’ ability in reading speed in extensive reading on semester III at FKIP UHN Pematangsintar. The method used in this research was quantitative research design. The population of this research is the students on semester III at FKIP UHN Pematangsiantar academic year of 2018/2019. Population of this research are 210 students. Sample of this research are two classes which are divided into control (group D) and experimental class (group E). The research instrument in the form of multiple choice test. There are 10 questions. After the data had been analyzed, the researcher concludes that the effect of speed reading technique on the students’ ability in comprehending a text was high. It was found that the value of t-test > t-table (1, 96 > 1, 67). It means that the use of speed reading technique on the students’ ability in comprehending a text is significant effective. Based on the result, it can be seen that the students’ reading comprehension ability increases. They can understand the passages easier and efficiently. Moreover, the students are not bored in learning English since the technique used. They can get maximum result with minimum effort.